Optimization of Community Products in Sukawarna Urban Village Through Digital Marketing Implementation and Website Development - Wulandari, Astri; Suryawardani, Bethani; Marcelino, Dandy; Rahman Wijaya, Dedy; Komala Sari, Siska; Gusnadi, Dendi; Suryana, Suryana (Ilin Institute, 2021)
In certain conditions, digital marketing is able to make it easy for businesses to monitor and provide all the needs and desires of potential customers. This means that in the digital marketing world, it discusses many things such as IT, social media, trends, netizens, business, advertising, and so on. Technological progress is a clear manifestation that consumer behavior has now shifted. The needs and desires that will be obtained are more practical and faster, as if it is becoming a trend in the society of “nowadays”. Society's need for information and the desire to be recognized as human beings are not ancient. Technological growth is increasing rapidly along with the availability of smartphones at affordable prices. Business opportunities in the virtual world described above should be explored and entered by various community businesses, even in small and micro scales. Including community businesses in Sukawarna Village which are engaged in small and micro medium enterprises (MSMEs). The purpose of implementing this community service activity is to increase the insight and competence of micro and medium entrepreneurs in Sukawarna Village in order to increase their insight into digital marketing.